MiR-221, miR-320a, miR133a, and miR-133b as potential biomarkers in leiomyosarcoma - Akhtar, Mst Nasrin; Walter, Annabell; Katenkamp, Kathrin; Chen, Yuan; Lehmann, Thomas; Weschenfelder, Wolfram; Spiegel, Christian; Vogt, Matthias; Hofmann, Gunther O.; Hochhaus, Andreas; Gaßler, Nikolaus; Clement, Joachim H.; et al. (Frontiers in Oncology, 2025)
BackgroundLeiomyosarcoma is an aggressive tumor with a high rate of distant metastasis and poor prognosis. No standardized biomarkers are available to assess early diagnosis or monitoring during the clinical course. MicroRNAs (miRNAs) function in modulating a multitude of targets and are involved in tumorigenesis, cancer progression, and metastasis. This study was designed to evaluate miR-221, miR-320a, miR-133a, and miR-133b as potential biomarkers in leiomyosarcoma.Materials and methodsThe expression levels of miR-221, miR-320a, miR-133a, and miR-133b as well as their target mRNAs CDKN1B, TGFBR1, and IGF1R were assessed by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) in tissue samples from 33 patients with leiomyosarcoma. Wilcoxon test, Kruskal-Wallis test, Mann-Whitney test as well as Spearman-Rho-test were used for statistical analysis. Receiver operating characteristic (ROC) analyses were performed to discriminate metastatic risk of local and primary tumors in correlation to miR-221, miR-320a, miR-133a, and miR-133b.Results and discussionThe expression levels of miR-221, miR-320a, and miR-133a were significantly upregulated in leiomyosarcoma tumor tissue compared to adjacent non-tumor tissue (p = 0.003 for miR-221, p = 0.006 for miR-320a, and p = 0.044 for miR-133a respectively). The target mRNAs CDKN1B, TGFBR1, and IGF1R in 25 leiomyosarcoma tumor tissues were not significantly deregulated. There was no significant upregulation in primary tumors and metastases compared to local tumors for miR-221, miR-320a, miR-133a, and miR-133b. ROC curves of miRNA-221, miR-320a, miR-133a, and miR-133b to predict metastatic risk at initial presentation of the tumor, comparing non-metastasizing and metastasizing leiomyosarcomas, demonstrated no significant levels.ConclusionmiR-221, miR-320a, and miR-133a were significantly upregulated in leiomyosarcoma tumor tissue as compared to adjacent non-tumor tissue. There was no significant difference in miRNA expression and ROC curves in primary tumors as compared to local tumors. While not statistically significant, ROC curve of miR-133b suggests a potential role in predicting metastatic risk, warranting subsequent analysis. This study provides evidence for further evaluation of miR-221, miR-320a, miR-133a, and miR-133b as biomarkers in primary diagnosis and assessment of metastatic risk in leiomyosarcoma.